Assessment of the Efficacy of Physical Activity Level and Lifestyle Behavior Interventions Applying Social Cognitive Theory for Overweight and Obese Girl Adolescents - Bagherniya, Mohammad (J Res Health Sci, 2018)
Background: Childhood obesity has become a global epidemic and physical inactivity and considered asone of the most important contributing factors. We aimed to evaluate a school-based physical activityintervention using social cognitive theory (SCT) to increase physical activity behavior in order to preventobesity among overweight and obese adolescent girls. Study design: Randomized controlled trial study. Methods: A seven-month randomized controlled trial based on SCT was implemented with 172overweight and obese girl students (87 in intervention and 85 in control group), with the presence of theirparents and teachers. Activities of the trial included: Sports workshops, physical-activity consulting privatesessions, free practical and competitive sports sessions, family exercise sessions, text messages, andnewsletters. Body Mass Index (BMI) and Waist Circumference (WC) were measured and questionnairesabout duration of physical activity, duration of screen time (watching television and playing computergames) and psychological variables regarding the SCT constructs were obtained. Results: Duration of physical activity (in minutes) and most of psychological variables (self-efficacy, socialsupport, and intention) significantly increased at post-intervention, while hours of watching television andplaying computer were significantly decreased (P<0.001). The subjects’ mean BMI and WC reduced inthe intervention group from 29.47 (4.05) kg/m2 to 28.5 (4.35) kg/m(2) and 89.65 (8.15) cm to 86.54 (9.76)cm, although they were not statistically significant compared with the control group (P=0.127 and PP=0.504,respectively). Conclusions: School-based intervention using SCT led to an increase in the duration of physical activityand reduction in the duration of screen time in overweight and obese adolescent girls.